USE OF DIGITAL EDUCATIONAL RESOURCES IN "TECHNOLOGY" CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article provides information about the use of digitized educational resources in "Technology" classes and the specific characteristics of digitized educational resources in the higher education system.